Whole Body Fluoro-Deoxy-Glucose Positron Emission Tomography in Pediatric Solid Pseudopapillary Epithelial Neoplasm - Bikkina, Pratyusha; Abubacker, Zakir A.; Ajit, Nimmagadda; Edamadaka, Yeshwanth (World Journal of Nuclear Medicine, 2025)
Solid pseudopapillary epithelial neoplasm (SPEN) is a rare pancreatic tumor primarily affecting adolescent girls and young women. While generally indolent, SPEN can exhibit locally aggressive behavior or distant metastases. Accurate preoperative characterization is essential for optimal management.
Keywords: FDG; SPEN; pancreas; PET; CBD